Antibacterial Activity of Ethanol Extract of Red Spinach Leaves (Amaranthus tricolor L.) Extracted Using Microwave-Assisted Extraction Against Pseudomonas aeruginosa and Streptococcus pyogenes - salim, Emil; Siregar, Syifa Sabila Yassarah; Keliat, Jane Melita (Talenta Publisher, 2024)
Background: Humans are among the most susceptible living beings to bacterial infections. Infectious wounds on the skin surface are easily colonized by various kinds of bacteria such as Pseudomonas aeruginosa and Streptococcus pyogenes. Red spinach (Amaranthus tricolor L.) contains flavonoids with antimicrobial properties. Objective: The aim of this study was to determine the antibacterial activity of ethanol extract of red spinach leaves (Amaranthus tricolor L.) against Pseudomonas aeruginosa and Streptococcus pyogenes. Methods: This research includes the preparation, characterization, phytochemical screening of dried powder and extract. Extraction was performed by microwave-assisted extraction (MAE) method using 70% and 96% ethanol variations and then antibacterial activity of ethanol extract of red spinach leaves against Pseudomonas aeruginosa and Streptococcus pyogenes bacteria was carried out by paper disc diffusion method (Kirby-Bauer test) to obtain the diameter of inhibition. Results: The 70% ethanol extract of red spinach leaves has the lowest concentrations of 0.78 mg/ml and 25 mg/ml against Pseudomonas aeruginosa and Streptococcus pyogenes bacteria with diameters of 7.23 mm, and 7.90 mm respectively. While the 96% ethanol extract of red spinach leaves has the lowest concentration of 0.78 mg/ml against Pseudomonas aeruginosa and Streptococcus pyogenes bacteria with a same diameter of 7.43 mm. Conclusion: Ethanol extract of red spinach leaves has antibacterial activity against Pseudomonas aeruginosa and Streptococcus pyogenes.